The Influence of Tax Awareness, Rationalization and Tax Service of Fiscus on Tax Payer Compliance (Study of Individual Taxpayers in the North Badung Pratama Tax Office Area) - Radja Ratu, Ikha Junisia Repenia; Wasita, Putu Aristya Adi; Artaningrum, Rai Gina (LPPM Universitas Dhyana Pura, 2025)
The government relies on tax revenue as the main source of development funds so that taxpayers are expected to have high tax compliance, but the reality shows that most taxpayers do not have compliance. This study is presented at the North Badung Pratama Tax Office. Sampling in this study was carried out by convenience sampling with a sample of 100 respondents. The data analysis technique used is multiple linear regression research with data presentation assisted by SPSS version 26. Through the results of the study, it is known that Tax Awareness has a positive effect on taxpayer compliance, Rational Attitude has a positive effect on taxpayer compliance and Fiscus Services have a positive effect on taxpayer compliance. Seeing the research study to improve taxpayer compliance, it is very necessary to pay attention to efforts to increase tax awareness, rational attitudes and fiscus services.